The Arrangement of Grammatical Affixes in Open Word Classes (Central Kurdish Dialect) - تاهر, دلمان قتاس (Tasnim International Journal for Human, Social and Legal Sciences, 2025)
This research titled "The Arrangement of Grammatical Affixes in Open Word Classes (Central Kurdish Dialect)" attempts to identify, according to the research title, which grammatical suffixes can be arranged sequentially and which word classes (parts of speech) can accept sequential Auffixes. To conduct this research, the following questions were determined: (Which grammatical Affixes can form sequences in word classes? Which word classes can accept sequential grammatical affixes? Which sequential grammatical affixes are more numerous in word classes and which are less? Which word classes are more capable of accepting sequential grammatical affixes and which are less?). This research, in addition to the introduction and conclusions, consists of two sections. The first section covers (Grammatical Affixes and Word Classes), which represents the theoretical aspect of the research and consists of two chapters. The first chapter, titled (Affix and Its Arrangement), includes (the concept of suffix, characteristics of suffix, classification of suffixes, types of suffixes), and the second chapter, titled (Sequential Affixes and Word Classes), includes (the concept of word class, characteristics of word class, open and closed word classes). The second section discusses (The Arrangement of Grammatical Affixes in Open Word Classes (Central Dialect as a Model)). In conclusion, the researcher found that the majority of verb grammatical affixes can be arranged sequentially, and the statistical method was used to identify affixes in the results.